LA COOPERACIÓN PUBLICO – PRIVADA EN EL DESARROLLO TURISTICO LOCAL - Medina, Edwin Vílchez (2010)
The article analyzes the factors that influence the dynamic generation of local tourism development. The dynamics of development involving the participation of institutions from local, regional and national levels, as well as the involvement of private business organizations. Therefore, it is necessary to study the factors, according to the dimensions of the  micro and  the macro environment, to a greater or lesser extent have an  impact on  the  success or  failure of business  projects,  protected  by  the use or mechanisms of public - private cooperation, with particular reference to our communities.